The Impact of Rice Production on the Gross Regional Domestic Product (GRDP) of the Agricultural Sector in Indonesia in 2024 - M. Ikhsan Nur Rozak; Yuli Safitri (Transpublika Publisher, 2025)
The agricultural sector occupies a pivotal position within the Indonesian economy, particularly in underpinning food sovereignty and galvanising regional economic advancement. From an Islamic economic standpoint, productive endeavours constitute an integral manifestation of earth stewardship (isti'mar al-ardh), as divinely ordained in QS. Hud: 61, and must be inexorably oriented toward the collective amelioration of societal welfare. This article aims to identify the bearing of rice cultivation output upon the Gross Regional Domestic Product (GRDP) of the agricultural sector across Indonesia in 2024. Employing a quantitative epistemological paradigm, this study draws upon secondary data procured from the Central Statistics Agency (BPS), encompassing cross-sectional observations spanning 38 provincial jurisdictions throughout Indonesia. The analytical instrumentation deployed is simple linear regression. Empirical findings corroborate that rice production exerts an affirmative and statistically consequential influence upon the agricultural sector's GRDP, evidenced by a probability value of 0.0000 (<0.05). The regression coefficient of 0.365528 denotes that an incremental augmentation in rice production is concomitantly accompanied by a commensurate ascendancy in agricultural GRDP. The coefficient of determination (R-squared) of 0.677635 substantiates that rice production explicates 67.76% of the observed variability in the agricultural sector's GRDP. Accordingly, rice cultivation output assumes an indispensable role in buttressing the operational performance of Indonesia's agricultural sector. This empirical corroboration affirms that the amplification of rice production not only catalyses macroeconomic proliferation but also resonates consonantly with the Islamic economic tenet of attaining comprehensive prosperity (falah) and overarching communal beneficence.